Miracles : the credibility of the New Testament accounts - Keener, Craig S. (Grand Rapids, Michigan : Baker Academic, 2011)
This study presents the most thorough current defense of the credibility of the miracle reports in the gospels and Acts. Drawing on claims from a range of global cultures and taking multidisciplinary approach to the topic, Keener suggests that many miracle accounts throughout the history and from contemporary times are best explained as genuine divine acts, lending credence to the biblical miracle reports.--from publisher description
Contents: v.1.pt.1. The ancient evidence. Opening questions about early Christian miracle claims; Ancient miracle claims outside Christianity; Comparison of Early Christian and other miracle accounts--pt. 2. Are miracles possible. Antisupernaturalism as an authenticity criterion; Hume and the philosophic questions; Developing Hume's skepticism toward miracles--pt.3. Miracle accounts beyond antiquity. Majority world perspectives; Examples from Asia; Examples from Africa, Latin America, and the Caribbean; Supernaturalism in earlier Christian history; Supernatural claims in the recent west; Blindness, inability to work, death, and nature: Some dramatic reports--v.2.pt.4. Proposed explanations. Nonsupernatural causes; Biased standards; More extranormal cases.
Keywords: Bible.N.T.Gospels -- Evidences, authority, etc; Bible.N.T.Acts -- Evidences, authority, etc; Miracles; Spiritual healing -- Christianity